Cost-effectiveness analysis of pembrolizumab versus chemotherapy as first-line treatment in locally advanced or metastatic non-small cell lung cancer with PD-L1 tumor proportion score 1% or greater. (December 2019) - She, Longjiang; Hu, Huabin; Liao, Mengting; Xia, Xuefeng; Shi, Yin; Yao, Linli; Ding, Dong; Zhu, Youwen; Zeng, Shan; Shen, Liangfang; Huang, Jin; Carbone, David P.
Highlights: Pembrolizumab provided quality-adjusted life year and life years. Pembrolizumab is cost-effective in PD-L1 TPS ≥ 50% populations. Pembrolizumab is not cost-effective in PD-L1 TPS ≥ 20% and 1% populations. Abstract: Objective: The purpose of this study was to estimate the cost-effectiveness analysis of pembrolizumab versus chemotherapy as first-line treatment in locally advance or metastatic non-small cell lung cancer (NSCLC) with programmed death ligand 1 (PD-L1) tumor proportion score (TPS) 1% or greater from the United States (US) payer perspective. Materials and Methods: This Markov structure was developed to estimate cost and effectiveness of pembrolizumab vs chemotherapy in the first-line treatment of locally advance or metastatic NSCLC based on the data from KEYNOTE-042. Cost and health outcomes were estimated at a willingness-to-pay (WTP) threshold of 150, 000 per quality adjusted life year (QALY) in three PD-L1 TPS populations (≥50%, ≥20% and ≥1%). One-way, two-way and probabilistic sensitivity analysis were to test the model stability. Subgroup analysis were performed in three PD-L1 TPS populations (≥50%, ≥20% and ≥1%). Results: The incremental costs and QALYs that pembrolizumab yielded, compared with chemotherapy, were 86164.87 and 0.63, 74562.25 and 0.46 and 70886.65 and 0.39 for the populations with a PD-L1 TPS ≥ 50%, TPS ≥ 20% and TPS ≥ 1%, leading an incremental cost-effective ratio (ICER) of 136, 228.82, 160, 625.98 and 179, 530.17 per QALY, respectively. Conclusion: First-line treatment with pembrolizumab is a cost-effective strategy compared with platinum-based chemotherapy when the value of WTP was 150, 000 per QALY in locally advanced or metastatic NSCLC patients with PD-L1 TPS ≥ 50% and without epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) mutations, but not in the TPS ≥ 20% and 1% populations.